Czech Republic : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper analyzes current developments and outlook for inflation in the Czech Republic. Inflation in the Czech Republic has fallen substantially since peaking in the double digits in 1998. The crisis-led depreciation of the koruna in mid-1997 pushed year-over-year inflation to more than 13 percent. The paper presents the IMF staff analysis that shows that without interest rate increases, inflation is likely to begin to rise above the midpoint of the Czech National Bank's target in mid-2005. The paper also analyzes the Czech labor market in a cross-country perspective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet